GFAP and S100B Protein are Associated with Discharged NIHSS of Anterior Circulation Ischemic Stroke - Yenny Surjawan; Suryani As'ad; Teguh A S Ranakusuma; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Patient with larger ischemic lesion will suffer more severe neurogical deficit. The utility of MRI for lesion size measurement is still limited, therefore additional approach was pursued through examination of markers released by damaged brain cell, GFAP and S100B protein. The aim of this study is to know whether both markers are associated with the neurological deficit of anterior circulation ischemic stroke. METHODS: This observational prospective study enrolled 74 patients with anterior circulation ischemic stroke diagnosis. GFAP and S100B protein were measured with ELISA using blood collected at 48 to 72 hours after onset. The neurological deficit was assessed with NIHSS ad discharged.RESULTS: There was a significant association between GFAP level and discharged NIHSS (p=0.008) with 100% sensitivity and 100% negative predictive value. S100B protein also showed a significant correlation with discharged NIHSS (r=0.488; p=0.000) and this correlation could be described with an equation (OR=1.009; 95% CI=1.0003-1.0188; p=0.044). S100B protein at 78.3215 ng/L would give true prediction as 73.9% (95% CI=62.7%-85.2%, p=0.001). CONCLUSIONS: GFAP and S100B protein that were measured at 48 to 72 hours after onset were significantly associated with NIHSS at discharge. KEYWORDS: GFAP, S100B protein, discharged NIHSS, ischemic stroke